Formation of Forest Management in Modern Japan: A Case Study of Muraoka-Cho, a Village in Hyogo Prefecture - FUKUDA, Satoshi (Japanese Sociological Review, 2004)
In recent years, the problem of forest preservation has often been the subject of debate. Internationally, the depletion of forest resources poses a problem, but in Japan, the maintenance of superfluous forest resources poses a problem. The purpose of this paper is to clarify the process of the formation of forest management in modern Japan through a historical analysis of the village as a basic unit of forest management and administration holding up an afforestation policy. Forest management has undergone a significant reform during modern Japan. Since the early modern Japan, the inhabitants of Muraoka-cho in Hyogo prefecture have utilized the communal forest for maintaining rural life. Afforestation was started during the second half of the Meiji era under historical conditions in which the interests of the forest administration corresponded with those of the residents, and this system of management formed the basis of the traditional maintenance of the communal forest. The significance of this historical study is as follows : first, afforestation was carried out in order to solve the forest problem of a modern kind. However, problems were already inherent in the very idea of afforestation. Second, the modern forest management not only produced the problem, but the social organization indispensable to residents.